(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
An estimated 55,000 people die of rabies every year1, and 99% of these are caused by bites from rabid dogs.2 The global economic burden of rabies is estimated to be 4,000M USD/year3. Mass dog culls are organized by governments in misguided attempts to control the disease and limit outbreaks however this approach has repeatedly been shown to be ineffective for rabies control4.These culls include gassing, shooting, electrocution, beating, and poisoning, cause the needless death of millions of dogs each year, furthermore such in humane methods are condemned internationally5. Conversely, evidence shows that vaccinating at least 70% of a dog population annually creates a barrier of healthy immune dogs that stops the disease from spreading.2 On World Rabies Day 2011, WSPA launched the Red Collar Campaign (RCC), which isa global campaign to end the inhumane culling of dogs in the fight against rabies. Our goal is to convince and assist governments to control rabies in an effective, humane, and sustainable way through mass vaccination without the in humane culling of dogs. Latin America (LA) is an example of best practice in rabies control as it has been committed to dog vaccination since the 80´s.Using this approach, dog rabies cases in LA declined from 25,000 in 1977 to196 in 2011, a decrease of 99% and subsequently , human rabies also fell to only15 in 2011, a decrease of 96%.6 Thus, mass vaccination of dogs has become an essential component in rabies control by halting disease spread, alongside pre and post-exposure prophylaxis, surveillance and informational campaigns. This commendable work reveals the importance of creating political will and provides inspiration to other regions to change their policy and practice. In2008, a rabies outbreak occurred in the previously rabies-free island of Bali, Indonesia, leading to a widespread dog cull. In 2010, in response to this unnecessary killing, WSPA worked together with the Bali Animal Welfare Association(BAWA) and convinced Bali’s government to stop killing dogs and implement the first island wide mass dog vaccination, reaching 70% coverage and saving over 300,000 dogs from a needless death. During this vaccination period, human rabies cases decreased by 35%, and dog cases by 76%.6 The Disease Investigation Centre in Bali reports that people in Indonesia now believe in the power of vaccination and the systems and procedures developed during WSPA and BAWA´s work in Bali are being adopted as national guidelines. In November 2011, WSPA supported the Bangladeshi government to carry out a pilot dog vaccination project in Cox’s Bazar, vaccinating more than 70% of the dog population in two weeks. WSPA is now working with the Government to develop a national action plan for eliminating rabies through mass dog vaccination. WSPA’s RCC has continued to gather global momentum since these successes, providing further evidence for the contribution of positive animal welfare to human health.